PENERAPAN PEMBELAJARAN LANGSUNG TERHADAP HASIL BELAJAR FISIKA PESERTA DIDIK KELAS XI IPA SMAN 1 ALLA’ KABUPATEN ENREKANG - Irwan S; Aisyah Azis; A Momang Yusuf (Jurnal Sains dan Pendidikan Fisika, 2016)
This research is a pre-experimental study. The purposes of this research are: (1) to determine the learning outcome of physics students of class XI IPA SMAN 1 Alla' in academics year 2013-2014 after taught by using direct instruction and (2) to determine whether the learning outcome of physics students taught using direct instruction has reached the classical completeness 85% of KKM assigned school. The variable in this research is learning outcome of physics students in class XI IPA SMAN 1 Alla '. The population of this research was students of class XI IPA SMAN 1 Alla' Enrekang regency in the second semester in academic year 2013-2014. The sample in this research as many as 47 students. Data were obtained by using the test results learners. Data were analyzed using descriptive statistical analysis. Descriptive statistical analysis of the research obtained by the percentage of students who achieve the standard minimum completeness criteria (KKM) amounted to 69.96% or 31 students out of 47 students. The results showed that the learning outcomes of physics students of class XI IPA SMAN 1 Alla ' in academic year 2013-2014 has not exceeded the classical completeness 85% set by the Ministry of Education and Culture after being taught by applying direct instruction.Key words: learning outcomes, direct instructionJenis penelitian ini adalah penelitian pra eksperimen. Tujuan penelitian ini adalah: (1)  untuk mengetahui besar hasil belajar fisika peserta didik SMA Negeri 1 Alla’ tahun ajaran 2013-2014 setelah diajar dengan menggunakan pembelajaran langsung dan (2) untuk mengetahui apakah hasil belajar fisika paserta didik yang diajar dengan menggunakan pembelajaran langsung telah mencapai ketuntasan klasikal 85% dari KKM yang ditetapkan sekolah. Variabel dalam penelitian ini adalah hasil belajar fisika peserta didik kelas XI IPA SMA Negeri 1 Alla’. Populasi penelitian ini adalah peserta didik kelas XI IPA SMA Negeri 1 Alla’ Kab. Enrekang pada semester genap tahun ajaran 2013-2014. Sampel dalam penelitian ini sebanyak 47 peserta didik. Data penelitian diperoleh dengan menggunakan tes hasil belajar peserta didik. Data yang diperoleh dianalisis menggunakan analisis statistik deskriptif. Hasil analisis statistik deskriptif diperoleh persentase peserta didik yang mencapai standar kriteria ketuntasan minimal (KKM) sebesar 69,96% atau 31 siswa  dari 47 siswa. Hasil penelitian menunjukkan bahwa hasil belajar fisika peserta didik kelas XI IPA SMA Negeri 1 Alla’ tahun ajaran 2013-2014 belum mencapai ketuntasan klasikal 85% yang ditetapkan Departemen Pendidikan dan Kebudayaan setelah diajar dengan menerapkan pembelajaran langsung.Kata Kunci:  hasil belajar, pembelajaran langsung